Examining the role of trade, consumption, and institutional quality in economic growth: Evidence from Southeast Asia - Basuki, Agus Tri; Pinjaman, Saizal (Jurnal Ekonomi & Studi Pembangunan, 2025)
This research is particularly important because Southeast Asia represents one of the most dynamic and heterogeneous regions in the world, with varying stages of economic development, institutional quality, and policy orientations. Despite its strong economic potential, the region faces structural challenges such as income inequality, governance issues, and external vulnerability. Understanding the long-run and short-run determinants of economic growth is therefore crucial for designing effective policies that sustain inclusive development. Previous studies have often focused on single-country analyses or employed models that capture only short-term relationships, leaving a gap in understanding the long-term equilibrium dynamics across Southeast Asian economies. By applying the Panel Error Correction Model (ECM), this study bridges that gap by integrating both temporal and cross-country perspectives. Moreover, incorporating variables such as Government Health Expenditure and Rule of Law allows the analysis to move beyond conventional macroeconomic factors, emphasizing the interplay between institutional quality, social investment, and economic performance. The results of this study provide not only empirical evidence but also practical insights for policymakers. Identifying the key drivers that influence economic growth both in the short and long run can guide governments in optimizing fiscal priorities, improving governance, and fostering sustainable industrial and trade strategies. In an era marked by global uncertainty and post-pandemic recovery, such evidence-based understanding is vital for promoting resilient and inclusive growth trajectories across Southeast Asia.